Thank you (falettinme be mice elf agin) : a memoir - Stone, Sly; Greenman, Ben; Hirschkowitz, Arlene (AUWA Books : MCD : Farrar, Straus and Giroux, 2023)
"The first memoir from the legendary Sly Stone, the front man of the iconic band Sly and the Family Stone"--